Aerobic potency of profissional futsal athlets of different competitive levels - Fin, Willian (2021)
The futsal is an intermittent sport that requires high technical, tactical and physical preparation from athlets. In order to give support to the high fisiologycal demand from plays, it is necessary an optimal physical conditioning from the players. The aim of this study is to compare the aerobic potency, in futsal athlets, from different competitive teams levels, in different tactical functions, evaluated by a specific test to the futsal sport, what is called Yo-Yo Intermittent Recovery Level one (YYIR1). Thirty athlets are evaluated, who played in three different divisions (gold series, n= 12; silver series, n=9 and bronze series, n=9), in futsal teams from Rio Grande do Sul, during the 2017 temporade. Significant differences are found in percured distance in Gold series 2148 (sd 292m); 1591 (sd 459m) in Silver category, and 1600 (sd 681m) in Bronze category. These results indicate that the aerobic potency demonstrate differences between the different levels of competitions. When individuals from the same tactical functions are compared, no significant differences are found, in relation to the aerobic potency. The differences point out that there are significant differences between the different competitive levels from Rio Grande do Sul, showing better results to the Gold level team. It indicates that athlets from higher competitive levels have more aerobic aptitude, possibly due to a higher training volume and higher physical exigency during the plays.